Qawaidh fiqhiyyah Sebagai Landasan Dalil Hukum Islam - Hasibuan, Mhd Saleh Hasibuan; Sinaga, Riyan Syaputra; Siahaan, M Raja; Ginting , Adrian seputro; Tambunan , Hanif Rahman (Tabayyun : Journal Of Islamic Studies, 2025)
Qawaid fiqhiyyah (rules of fiqh) have a very important role in the development of Islamic law, because they provide the basic basis for determining and applying legal arguments in various contexts. This article discusses the role of qawaid fiqhiyyah as a guide in understanding and formulating the postulates of Islamic law, as well as how they are applied in solving contemporary fiqh problems. These fiqh rules, such as "al-umur bimaqasidiha" (everything is judged based on its purpose) and "la darar wa la dirar" (should not cause harm), function as universal principles that allow flexibility in responding to social developments and changing times. Through the application of qawaid fiqhiyyah, ulama and fuqaha can carry out ijtihad and produce fatwas that suit the needs of society without violating the basic principles of sharia. Therefore, qawaid fiqhiyyah is an important basis for enforcing Islamic law that is relevant and applicable in various life situations. This article also examines how qawaid fiqhiyyah functions in ensuring the continuity and relevance of Islamic law in facing the challenges of modernity.